(untitled) (Research, Society and Development, 2020)
The objective was to describe the scientific evidence that analyzes the relationship of STIs in women deprived of their liberty, as well as the impact of the disease and risk factors in female prisons for this population. an integrative literature review study was carried out, with a descriptive qualitative approach. articles published in the databases Pubmed, Google Scholar (Google Scholar), Scientific Eletronic Library Online (SciElo) and Virtual Health Library (BVS), published in the period from 2015 to 2019, were searched using the descriptors: “Sexually Transmitted Infections”, “Women’s Penitentiary” and “Nursing”. 89 articles were found, of these, 13 were used to construct the article. The articles were divided into two thematic axes of greatest interest, the first deals with the prevalence of STIs in women’s prisons, with 5 articles, thus realizing that there are still few articles dedicated to analyzing the prevalence of STIs in female inmates; the second deals with the factors associated with the contamination of women incarcerated by STIs, for which 11 articles were found, demonstrating that there are many vulnerability factors that increase the occurrence of diseases within female prisons. It is concluded that in view of the high prevalence of sexually transmitted infections in the prison environment, the identification of sociodemographic characteristics and risk behaviors undertaken by incarcerated women are important for understanding this problem.